NUTRITIONAL INTERVENTION FOR ENHANCING THE REPRODUCTIVE PERFORMANCE OF CROSSBRED PIGS - GOPINATHAN, A; KARTHICKEYAN, S M K; RAMESH, J; SIVASELVAM, S N (The Indian Journal of Animal Reproduction, 2023)
The study was carried out to assess the effect of nutritional intervention in the feeding regimen of crossbred pigs (N=21) on the reproductive performances such as litter size at birth and at weaning, litter weight at birth and at weaning, birth and weaning weight and pre-weaning mortality. Twenty one crossbred sows aged more than one year and farrowed once, were taken for the .study in Pig Breeding Unit functioning at Livestock Research Station, Kattuapkkam. The standard feeding protocol was designed taking into consideration of dewormers, vitamins and minerals mixture and calcium supplementation along with normal concentrate feeding. The results showed highly significant differences (P<0.01) in litter weight at birth and at weaning, while litter size at birth and at weaning and birth weight differe? significantly (P<0.05). Thus, nutritional inteivention used as a standard protocol in the feeding regimen of pigs would be helpful to augment the reproductive performance in field conditions.